Incorporation of lithium halogen in Li7P3S11 glass-ceramic and the interface improvement mechanism. (10th September 2021) - Zhao, Bing; Wu, Juan; Wang, Zhixuan; Ma, Wencheng; Shi, Yaru; Jiang, Yong; Jiang, Jinlong; Liu, Xiaoyu; Xu, Yi; Zhang, Jiujun
Highlights: The influence of halogens incorporation on Li7 P3 S11 glass-ceramic is studied. 80Li7 P3 S11 20LiBr shows improved ability to suppress lithium dendrites. LiBr does not enter the lattice, but rather exists in the lattice gap of Li7 P3 S11 . Br decrease electron cloud density on P and S, reduce Li + binding and increase ion conductivity. DFT evaluations prove that LiBr incorporation increases interface energy of SEI to Li. Abstract: Li7 P3 S11 glass-ceramic is considered as a superionic conductor electrolyte with great application prospect, but its realization is limited due to an unstable interface against lithium metal. Incorporation of lithium halides in electrolyte promotes enhancement in ionic conductivity and helps inhibit lithium dendrite growth. However, the mechanistic impact of halide incorporation is still not been fully explained. In this work, the effects of halogen introduction into Li7 P3 S11 glass-ceramic to the ion conductivity, critical current density and interfacial stability of solid electrolyte interphase (SEI) is studied. It shows that the LiBr-incorporated Li7 P3 S11 obtains the most obviously increased critical current density. Structural characterizations indicate that the LiBr does not enter the lattice, but rather exists in the lattice gap of Li7 P3 S11 . However, the highly electronegative Br decreases the electron cloud density on the surface of P2 S7 4− and PS4 3− units, reduces their binding to Li + and thus increases the ion conductivity. Density functional theory evaluations show that the addition of LiBr can increase the interface energy of SEI to Li, which is beneficial to suppress the growth of lithium dendrite. Therefore, the Li/80Li7 P3 S11 20LiBr/Li cell presents a double increase of the critical current density (0.968 mA/cm 2 ) and circulates stably at 0.5 mA/cm 2 at room temperature. Graphical abstract: The effects of halogen introduction into Li7 P3 S11 glass-ceramic to the ion conductivity and interfacial stability of SEI is studied. Image, graphical abstract